Evidence of Xyleborinus attenuatus (Blandford 1894) (Coleoptera: Curculionidae: Scolytinae: Xyleborini) populations in Quebec, Canada - Popa, Valentin; Guertin, Claude; Werbiski, Robert (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2014)
Six species of the genus Xyleborinus (Reitter 1913) have been reported in North America. Five of these species were introduced, and one species is considered native to North and South America. Xyleborinus attenuatus (Blandford 1894), which was introduced into the Americas from Asia, was first recorded in 1995 in western Canada, in the province of British Columbia, and then in 2007 in the province of Nova Scotia, in eastern Canada. In Quebec, X. attenuatus was initially recorded in 2009 based on a single captured specimen. In this study, we present additional evidence of the presence of this alien ambrosia beetle in Quebec, Canada.